Determination of Type 2 Diabetes Risk by Using of Diabetes Risk Questionnaire Prepared by Turkish Diabetes Association in People Living in the District of Zeytinburnu, Istanbul - Gülay Karakaş; Neda Taner; Çağlar Macit (Research Center for Rational Use of Drugs (RCRUD), 2021)
Background: Type 2 diabetes is a serious condition that is rapidly increasing all over the world and can cause other metabolic diseases. In our study, we aimed to evaluate the probability of the participants having Type 2 diabetes by using diabetes risk questionnaire. Methods: During the month of March 2019, a validated questionnaire prepared by the Turkish Diabetes Association was administered to 500 patients (M= 223, (44.6%); (F= 277), (55.4%)) who were applying to a pharmacy in Zeytinburnu, Istanbul. Statistical analyzes were performed using SPSS version 21. Data were expressed as mean, standard deviation (SD) and percentage (%). In this respect, the normality of data distribution was determined by the Shapiro-Wilk test. Results: The scale total scores of women were significantly lower than the total scale scores of men (p<0.001). It was found that the risk of developing diabetes increased significantly with age (p <0.001). Patients aged 60 and over were at the highest risk of Type 2 diabetes. It was determined that the risk of developing Type 2 diabetes was significantly higher in patients with high blood pressure (n= 111), (p<0.001). One hundred and thirty-seven physically inactive participants had a significantly higher risk of Type 2 diabetes (p<0.001). Finally, the risk of diabetes increased with increasing weight (p <0.001). Conclusion: In conclusion, increasing age, high blood pressure, physical inactivity can increase the risk of Type 2 diabetes. To prevent the risk, people should be physically active and they should consume healthy and balanced diet.